Diagnosis dan Tata Laksana Eritroderma - Misturiansyah, Nurrul Izza; Miranti, Umi; Nuridah, Ayu Lilyana; Amien, Muhammad Irsyad; Yoga, R. Ristianto (Cermin Dunia Kedokteran, 2024)
Erythroderma, also known as exfoliative dermatitis, is a diffuse inflammation-related skin disorder characterized by redness and scales affecting more than 90% of the body surface area. Its incidence is around 1 per 100,000 adults, with a mortality rate of 16% each year, especially in immunodeficient patients. Several conditions as the main cause include psoriasis (23%), atopic dermatitis (16%), drug hypersensitivity reactions (15%), and cutaneous T-cell lymphoma (CTCL) or Sezary syndrome (5%). Erythroderma is a potentially life-threatening condition requiring diagnosis, identification of the etiology, and appropriate management.